Meter as a Prism. Interpreting a Theme in Sibelius’s Violin Concerto - Leong, Daphne (Revue musicale OICRM, 2025)
The lyrical second theme in the first movement of Sibelius’s Violin Concerto presents a metric conundrum: it is notated and barred in two distinct ways. One measure of 6/4 in the exposition corresponds to two measures of 2/2 in the recapitulation. This essay in multimedia modular format explores the meaning of the metric distinction, considering 1904 and 1905 versions of the concerto and Sibelius’s correspondence; performances and performing editions; and form and meter, tempo notated and performed, and elements of resolution. A shift in metric ground, change in the way tempo is slowed down, and homecomings in key, rhythm, and instrumental color all point to a recapitulatory second theme that flows differently—more spaciously and freely—than its expository twin.